Management of Vegetation by Alternative Practices in Fields and Roadsides - Allen V. Barker; Randall G. Prostak (International Journal of Agronomy)
In attempts to reduce the amounts of conventional herbicides used, alternative practices are sought in the management of roadside vegetation. In this investigation, alternative herbicides (citric-acetic acids, clove oil, corn gluten meal, limonene, and pelargonic acid), flaming, and mulching were assessed in management of annual and perennial, herbaceous vegetation in field and roadside plots. Several formulations of alternative herbicides applied singly or repeatedly during the growing season were evaluated and compared with conventional herbicides (glyphosate and glufosinate ammonium) or with flaming or mulching. Citric-acetic acid formulations, clove oil, limonene, or pelargonic acid applied as foliar sprays immediately desiccated foliage, but the efficacy lasted for no longer than five weeks. Repeated applications were better than single applications of these herbicides in suppressing plant vegetative growth. Corn gluten meal imparted little or no early control and stimulated late-season growth of vegetation. A single flaming of vegetation gave no better control than the alternative herbicides, but repeated flaming strongly restricted growth. Mulching with wood chips or bark gave season-long suppression of vegetation. Glyphosate gave season-long inhibition of vegetation, but the efficacy of glufosinate ammonium waned as the growing season progressed. For season-long suppression of vegetation with alternative herbicides or flaming repeated applications will be required.